2020
DOI: 10.3126/janr.v3i2.32301
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency of rice production in terai district of Nepal

Abstract:  This paper aimed to estimate the technical efficiency of rice production, also identifying the factors affecting technical efficiency. Jhapa, the Terai district of Nepal, having the highest rice production in the country, was purposely selected for the study. The primary information was collected from 100 rice growing farmers, randomly selected from the sampling frame, using the pre-tested semi-structured interview schedule. Also, two Key Informant Surveys were done. Besides, the secondary information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The estimated 0.369 coefficient for labor working hours was positive and highly significant (α= 0.000), ranked as the highest among all the other coefficients which revealed that a 1 percent increase in the labor hours raised the rice yield roots by nature and according to Arora et al (2019) it requires intensely ploughed soil to enter the feeding zones and get the desired amount of water, minerals and other nutrients easily. The results for tractor hours are in coherence to that of Subedi et al (2020), Bempomaa et al (2014), Ali and Munir (2014) and Reddy and Sen (2004). The coefficient estimated for weedicides and pesticides revealed that increase in the chemicals' application had a positive and significant effect of 0.06 percent on rice productivity.…”
Section: Sfm (Model-1) Estimatessupporting
confidence: 77%
“…The estimated 0.369 coefficient for labor working hours was positive and highly significant (α= 0.000), ranked as the highest among all the other coefficients which revealed that a 1 percent increase in the labor hours raised the rice yield roots by nature and according to Arora et al (2019) it requires intensely ploughed soil to enter the feeding zones and get the desired amount of water, minerals and other nutrients easily. The results for tractor hours are in coherence to that of Subedi et al (2020), Bempomaa et al (2014), Ali and Munir (2014) and Reddy and Sen (2004). The coefficient estimated for weedicides and pesticides revealed that increase in the chemicals' application had a positive and significant effect of 0.06 percent on rice productivity.…”
Section: Sfm (Model-1) Estimatessupporting
confidence: 77%
“…Irrigation assists plants to absorb nutrients available in the soil which increased production (Abbas, 2012). Likewise, Fatima (2010) revealed that several irrigations applied to the wheat crop had a positive impact on wheat production. Furthermore, Hussain et al (2012) in Pakistan found that irrigation application had a positive effect on wheat productivity.…”
Section: Resultsmentioning
confidence: 99%
“…The Azolla sp application improved nitrogen (15-20%), potassium value (16 %), and cation exchange capacity (2-3 %) from soil-contaminated Pb. Subedi & Shrestha (2015) stated that the application of Azolla has been found to improve the physical and chemical properties of the soil and the microbial population of the soil. Azolla application treatments with doses 0, 20, 40, 60 and 80 g kg -1 soil in all incubation times at 2, 4, 6, and 8 weeks simultaneously increased the value for soil N (Awodun, 2008).…”
Section: Soil Chemical Valuementioning
confidence: 99%